Penerapan Kebijakan MBKM Pada Mutu Pendidikan Mahasiswa di Universitas Yudharta Pasuruan - Ubaidillah, Muhammad; Shobri, Muwafiqus (Al Hikmah: Jurnal Studi Keislaman, 2023)
Abstract, This research aims to describe one implementation of the MBKM policy which is designed to help students optimally in one choice to focus on appropriate scientific competencies. In an implementation of MBKM decision making on the quality of student education at Yudharta Pasuruan University. A concept that promotes independent learning and efforts to prepare graduates in higher education to be ready to face global developments and changing times. This research uses a qualitative approach. with this type of analytical phenomenon research. Meanwhile, the data collection procedure is a case study in collecting data as the main source of this research so that this research has high validation according to what happens in the field. The results of this research show that the implementation of MBKM at Yudharta Pasuruan University includes: 1) MBKM policy planning on educational quality through student exchanges, and 2). implementation of MBKM policies on educational quality through student exchanges Keywords: MBKM policy, quality of student education